Secondary Specialized Educational Institutions of Tyumen in 1920—1930s - E. V. Borodulina; A. V. Skochin (Научный диалог)
Issues related to the material and personnel aspects in the initial period of the formation of secondary specialized educational institutions in Tyumen in the 1920—1930s are considered. Attention is paid to the study of the process of creating a network of educational institutions, areas of student training are identified, and data on the dynamics of the number of students are given. The analysis results of the material base of technical schools formation are presented. The problems that students had to face in the learning process were identified. An assessment of the material and technical conditions of educational activities is made. The authors dwell on the study of the staff of secondary specialized educational institutions of the city. Attention is paid to the analysis of the level of education and qualifications of teachers. The material working conditions of the teaching staff are investigated. The authors note a certain dynamics in solving the material and personnel problems of technical schools in the period under study, despite the fact that the existing opportunities of educational institutions were significantly inferior to the needs of the population in obtaining professional education. The conclusion is made about the degree of provision of educational institutions of the city with teaching and administrative personnel. The impact of this problem on the quality of student training is assessed.